Controlled pipeline lateral buckling by reeling induced curvature imperfections. (May 2021) - Zhang, Weihan; Kyriakides, Stelios
Abstract: Expansion of pipelines installed on the sea floor due to the passage of high temperature and pressure hydrocarbons leads to lateral buckling. Interaction with a frictional sea floor can result in localization of such buckles, which must be controlled to ensure that the local bending is within acceptable limits. Periodic geometric imperfections introduced to a pipeline installed by reeling using the Residual Curvature Method are modeled and their effectiveness as expansion loops is evaluated. The imperfections are generated by allowing chosen lengths of the line to retain a small curvature by judicious action at the straightener. The model properly accounts for the complex interactions between geometric and material nonlinearities with frictional forces. It is demonstrated that as the temperature increases, the line can buckle in a snap-through manner, or can grow stably usually causing plastic deformation in its crest. The behavior is governed by the length, curvature, amplitude and periodicity of the imperfection, and by the lateral and axial frictional forces that develop. The effect of each of these variables is studied parametrically. Overall, the Residual Curvature Method is found to be a viable and effective method of controlling lateral buckling. The results provide guidance on the optimal periodicity, how to avoid snap-through buckling, and how to simultaneously minimize plastic bending. Highlights: Thermal expansion of pipelines on the seabed caused lateral buckling. The Residual Curvature Method introduces periodic geometric imperfections. Reeling induced imperfections can control lateral buckling. Analysis demonstrates how to avoid snap-through buckling and minimize plastic bending.